(untitled) (Nigerian Journal of Technology, 2015)
Evaluation of palm kernel oil, cotton seed oil and olive oil as quenching media of 0.509Wt%C medium carbon steel was investigated. To compare the effectiveness of the oils, the samples were also quenched in water and SAE engine oil which are the commercial quenchants. The samples were quenched to room temperature in the quenching media (palm kernel oil, cotton seed oil and olive oil). The machined specimen of the steel was heated at 8800Cthen quenched in water, engine oil, palm kernel oil, cotton seed oil and olive oil. Tensile strength, hardness and impact energy were used to measure the quenching effectiveness of the various media. The microstructures and mechanical properties of the quenched samples were used to determine the quench severity of the oils. The test of the mechanical properties shows that the hardness of steel quenched in water was (1740.54 HBN), while the hardness of steel quenched in palm kernel oil was (740.34 HBN) which was recorded as the least in all samples quenched. As-received sample absorbed the highest amount of energy (183.10J) before fracture while sample quenched in water absorbs the least energy (28.50J). The microstructure of the samples quenched in the oils under study revealed the formation of low proportions of martensite and in the case of olive oil, there was retained austenite. Hence, olive oil can be used where cooling severity less than that of water and SAE 40 engine oil is required for hardening of plain carbon steels. http://dx.doi.org/10.4314/njt.v34i3.12